# Rewrite this function...

• Sep 27th 2010, 10:43 PM
yess
Rewrite this function...
write f(x) = (2x^3 -7)^5 as 2 simpler functions
• Sep 28th 2010, 02:51 AM
CaptainBlack
Quote:

Originally Posted by yess
write f(x) = (2x^3 -7)^5 as 2 simpler functions

Does this mean rewrite $f(x)$ as:

$f(x)=g(h(x))$

where $g$ and $h$ are in some sense simpler?

CB
• Sep 28th 2010, 02:51 AM
downthesun01
You're question is kind of vague. Are you looking for something like this?

$f(x)=g(h(x))$
• Sep 28th 2010, 07:49 AM
yess
Quote:

Originally Posted by CaptainBlack
Does this mean rewrite $f(x)$ as:

$f(x)=g(h(x))$

where $g$ and $h$ are in some sense simpler?

CB

yes sorry thats what i meant!
• Sep 28th 2010, 09:31 AM
CaptainBlack
Quote:

Originally Posted by yess
yes sorry thats what i meant!

Quote:

Originally Posted by yess
write f(x) = (2x^3 -7)^5 as 2 simpler functions

Quote:

Originally Posted by CaptainBlack
Does this mean rewrite $f(x)$ as:

$f(x)=g(h(x))$

where $g$ and $h$ are in some sense simpler?

CB

'

How about $h(x)=x^3$, then $g(x)=(2x-7)^5$ or maybe something simpler yet?

CB
• Sep 28th 2010, 02:03 PM
downthesun01
Shouldn't it be:

$f(x)=g(h(x))$

Where

$g(x)=x^{5}$ and $h(x)=(2x^{3}-7)$
• Sep 28th 2010, 03:24 PM
CaptainBlack
Quote:

Originally Posted by downthesun01
Shouldn't it be:

$f(x)=g(h(x))$

Where

$g(x)=x^{5}$ and $h(x)=(2x^{3}-7)$

There is no unique solution.

CB